The Haupttreuhandstelle Ost, the Treuhandstelle Posen and the expropriation of property during World War II - Dingell, Jeanne (Studia Historiae Oeconomicae, 2001)
The Haupttreuhandstelle Ost (HTO), Treuhandstelle Posen (TO Posen) was an active "trustee" agency of the German Reich 1939-45. The Berlin headquarters of the HTO, its TO Posen and the other subordinate branch offices in the eingegliederten Gebieten (annexed Polish territories) were called into being through Göring's ministerial decree from the 19. October 1939. The HTO was subordinate to the Vierjahresplan (the four year plan) and was intended to be not only a colonisation instrument, but also a means to pillage the annexed territories for the Nazi war machine.